Activation of lymphocytes induced by bronchial epithelial cells with prolonged RSV infection. - Ling Qin (Public Library of Science (PLoS), 2011)
Respiratory syncytial virus (RSV) preferentially infects airway epithelial cells,which might be responsible for susceptibility to asthma; however, the underlying mechanism is not clear. This study determined the activation of lymphocytes and drift of helper T (Th) subsets induced by RSV-infected human bronchial epithelial cells (HBECs) in vitro. HBECs had prolonged infection with RSV, and lymphocytes isolated from human peripheral blood were co-cultured with RSV-infected HBECs. Four groups were established, as follows: lymphocytes (group L); lymphocytes infected with RSV (group RL); co-culture of lymphocytes with non-infected HBECs (group HL); and co-culture of lymphocytes with infected HBECs (group HRL). After co-culture with HBECs for 24 hours, lymphocytes were collected and the following were determined in the 4 groups: cell cycle status; apoptosis rate; and concentrations of IL-4, IFN-γ, and IL-17 in the supernatants. Cell cycle analysis for lymphocytes showed a significant increase in S phase cells, a decrease in G1 phase cells, and a higher apoptosis rate in group HRL compared with the other three groups. In group HRL, the levels of IL-4, IFN-γ, and IL-17 in supernatants were also higher than the other three groups. For further study, lymphocytes were individually treated with supernatants from non-infected and RSV-infected HBECs for 24 h. We showed that supernatants from RSV-infected HBECs induced the differentiation of Th2 and Th17 subsets, and suppressed the differentiation of Treg subsets. Our results showed that HBECs with prolonged RSV infection can induce lymphocyte proliferation and apoptosis, and enhance the release of cytokines by lymphocytes. Moreover, subset drift might be caused by RSV-infected HBECs.